2019
DOI: 10.4103/jpbs.jpbs_5_19
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy of Aloe vera, lemon, Ricinus communis, and calcium hydroxide as intracanal medicament against Enterococcus faecalis: A confocal microscopic study

Abstract: Introduction: The aim of this study was to evaluate the antimicrobial efficacy of different intracanal medicaments against Enterococcus faecalis using confocal microscopy. Materials and Methods: Eighty extracted single-rooted mandibular premolar teeth were used in this study, which were decoronated and instrumented with K-files following which biomechanical preparation was performed up to ProTaper F3. The teeth were inoculated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…In total, 12 full-text articles were read thoroughly according to the inclusion criteria from the other method reference folder, and the remaining 18 studies that met the eligibility criteria adequately were from the main databases; no study from the “other method reference” folder was included. The final 18 studies were included in the qualitative analysis ( Abbaszadegan et al, 2016 , Athiban et al, 2012 , Babaji et al, 2016 , Bazvand et al, 2014 , Bhardwaj et al, 2012 , Ehsani et al, 2013 , Eskandarinezhad et al, 2022 , Ghasemi et al, 2020 , Goud et al, 2018 , Ismail et al, 2020 , Karkare et al, 2015 , Noushad et al, 2017 , Ramamurthy et al, 2017 , Sahebi et al, 2014 , Sailaja et al, 2020 , Valera et al, 2013 , Vasudeva et al, 2017 , Vinothkumar et al, 2013 ), and nine studies were included in the meta -analysis ( Bazvand et al, 2014 , Bhardwaj et al, 2012 , Eskandarinezhad et al, 2022 , Ghasemi et al, 2020 , Goud et al, 2018 , Sahebi et al, 2014 , Sailaja et al, 2020 , Valera et al, 2013 , Vasudeva et al, 2017 ). The agreement between reviewers was evaluated with the support of statistics ( Landis and Koch, 1977 ), which showed a high agreement (0.75) among them.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 12 full-text articles were read thoroughly according to the inclusion criteria from the other method reference folder, and the remaining 18 studies that met the eligibility criteria adequately were from the main databases; no study from the “other method reference” folder was included. The final 18 studies were included in the qualitative analysis ( Abbaszadegan et al, 2016 , Athiban et al, 2012 , Babaji et al, 2016 , Bazvand et al, 2014 , Bhardwaj et al, 2012 , Ehsani et al, 2013 , Eskandarinezhad et al, 2022 , Ghasemi et al, 2020 , Goud et al, 2018 , Ismail et al, 2020 , Karkare et al, 2015 , Noushad et al, 2017 , Ramamurthy et al, 2017 , Sahebi et al, 2014 , Sailaja et al, 2020 , Valera et al, 2013 , Vasudeva et al, 2017 , Vinothkumar et al, 2013 ), and nine studies were included in the meta -analysis ( Bazvand et al, 2014 , Bhardwaj et al, 2012 , Eskandarinezhad et al, 2022 , Ghasemi et al, 2020 , Goud et al, 2018 , Sahebi et al, 2014 , Sailaja et al, 2020 , Valera et al, 2013 , Vasudeva et al, 2017 ). The agreement between reviewers was evaluated with the support of statistics ( Landis and Koch, 1977 ), which showed a high agreement (0.75) among them.…”
Section: Resultsmentioning
confidence: 99%
“…Each root canal was inoculated with E. faecalis suspension using a sterile insulin syringe and incubated at 37 °C for 21 days under aseptic aerobic conditions. The inoculation was repeated every 3 days to ensure the viability of the bacteria [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…An inhibitory effect of aloe on the growth of Pseudomonas aeruginosa, Enterococcus faecalis, Helicobacter pylori, Escherichia coli and the fungi Candida albicans and the formation of biofilm by methicillin resistant Staphylococcus aureus (MRSA) has been demonstrated [11,13]. The antimicrobial activity of A. vera against E. faecalis is attributed to anthraquinones [13].…”
Section: Plants With High Antimicrobial Potentialmentioning
confidence: 99%
“…An inhibitory effect of aloe on the growth of Pseudomonas aeruginosa, Enterococcus faecalis, Helicobacter pylori, Escherichia coli and the fungi Candida albicans and the formation of biofilm by methicillin resistant Staphylococcus aureus (MRSA) has been demonstrated [11,13]. The antimicrobial activity of A. vera against E. faecalis is attributed to anthraquinones [13]. Studies conducted by Tariq et al have shown that some tested fractions of A. vera, differing in total phenolic content (TPC) and total flavonoid content (TFC), significantly inhibit the growth of P. aeruginosa (MIC 0.70, 0.71, 7.72, 8.68 μg/ml) [10].…”
Section: Plants With High Antimicrobial Potentialmentioning
confidence: 99%